Stimulus processing and error monitoring in more‐able kindergarteners with autism spectrum disorder: a short review and a preliminary Event‐Related Potentials study. (8th June 2017) - Kim, So Hyun; Grammer, Jennie; Benrey, Nurit; Morrison, Frederick; Lord, Catherine
Abstract: Deficits in executive functions (EF) in individuals with autism spectrum disorder (ASD) have been identified. However, there is limited evidence about patterns of deficits in EF‐related skills, especially at the neurobiological level, in young children with ASD and little is known about how these skills are related to other domains of functioning and symptom severity. In this study, we provide a focused review of EF‐related Event‐Related Potentials (ERP) studies in children with ASD, accompanied by preliminary data for neurophysiological correlates of EF on a child‐friendly Go/No‐go task. We focus our preliminary investigation on ERPs associated with stimulus processing (N2, P3) and error monitoring [error/correct‐related negativity (ERN, CRN), error positivity (Pe)] in 5‐year‐old kindergarteners with ASD and typical controls matched on age, gender and task accuracy. Children with ASD showed significantly greater amplitudes of ERN/CRN compared to matched controls, suggesting heightened response monitoring. The ASD group also showed less distinct inhibitory P3 compared to the TD group, potentially suggesting atypical stimulus processing. In children with ASD, higher autism symptom severity was correlated with larger P3. Better behavioral performance on an EF‐related task was correlated with smaller CRN. Our study is the first investigation to demonstrate the presence of N2, P3, ERN/CRN and Pe in kindergartners with ASD. The potential links between ERP patterns and behavioral and clinical features in more‐able children with ASD highlight the need for further exploration into the functional mechanisms of these atypical neural activities and for more focused behavioral interventions targeting cognitive control and response monitoring. Abstract : We provide a focused review of executive function (EF)‐related Event‐Related Potentials (ERP) studies in children with Autism Spectrum Disorders (ASD), accompanied by preliminary data showing significantly enhanced error/correct‐related negativity (ERN, CRN) and less distinct inhibitory P3 in kindergartners with ASD compared to typically developing children. These atypical ERP patterns were also associated with performance on an EF‐related task and autism symptom severity.